2015
DOI: 10.2967/jnumed.115.158055
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Dynamic 11C-Phenytoin PET Studies

Abstract: The overexpression of P-glycoprotein (Pgp) is thought to be an important mechanism of pharmacoresistance in epilepsy. Recently, 11 C-phenytoin has been evaluated preclinically as a tracer for Pgp. The aim of the present study was to assess the optimal plasma kinetic model for quantification of 11 C-phenytoin studies in humans. Methods: Dynamic 11 C-phenytoin PET scans of 6 healthy volunteers with arterial sampling were acquired twice on the same day and analyzed using single-and 2-tissue-compartment models wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Transport of the antiepileptic drug phenytoin by the human P-gp was shown to be extremely weak compared with the rodent isoform (23,24) and is hardly detected using a bidirectional transport assay (16). 11 C-phenytoin PET is nonetheless an elegant strategy to study antiepileptic drug disposition in the brains of patients with pharmacoresistant epilepsy, which may involve parameters other than P-gp at the BBB (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Transport of the antiepileptic drug phenytoin by the human P-gp was shown to be extremely weak compared with the rodent isoform (23,24) and is hardly detected using a bidirectional transport assay (16). 11 C-phenytoin PET is nonetheless an elegant strategy to study antiepileptic drug disposition in the brains of patients with pharmacoresistant epilepsy, which may involve parameters other than P-gp at the BBB (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, prior studies using 18 F-FCWAY found decreased uptake in the temporal lobe of patients with drug-resistant epilepsy (Theodore et al, 2007), which may have been caused in part by increased expression of P-gp. As a further example, Mansor and colleagues recently reported the synthesis of 11 C-phenytoin, an anti-epileptic drug that often leads to resistance (Mansor et al, 2015). Although phenytoin is a substrate for both P-gp and BCRP, its brain uptake would surely be a direct measure of resistance at least to this medication and perhaps others that are associated with drug resistance (Nakanishi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The AIC fraction was also calculated by measuring the frequency of AIC preferences for each model across all subjects (17). AIC was calculated for the following brain regions: frontal, temporal, parietal, and occipital lobes; whole brain; posterior cingulate; thalamus; striatum; brain stem; medial temporal lobe; hippocampus; and cerebellum.…”
Section: Kinetic Modelingmentioning
confidence: 99%